Biomechanical Study of the Pullout Resistance in Screws of a Vertebral Fixation System. (15th October 2011) - Fakhouri, Sarah F.; Zamarioli, Ariane; Wichr, Célia R. G.; Araujo, Cleudmar A.; Defino, Helton L. A.; Shimano, Antônio C.
Abstract : The purpose of this study was to investigate the effect of varying the outer diameter of screws of a vertebral fixation system by submitting them to mechanical tests and photoelasticity. The pullout mechanical test was performed in 20 swine lumbar vertebrae, divided into two groups based on the screw outer diameter: 5.0 and 6.0 mm. The maximal pullout strengths and stiffness were evaluated. For the photoelasticity, eight models were used and divided into the same groups. The maximal pullout strength was 974.12 ± 144.44 N in the 5.0 mm screws and 1537.42 ± 326.95 N in the 6.0 mm screws ( P < 0.001). The stiffness was 418.60 ± 62.58 10 3 N/m in the 5.0 mm screws and 502.12 ± 133.45 10 3 N/m in the 6.0 mm screws ( P = 0.09). The mean ± SD shear stress of the 5.0 mm screws was 12.90 ± 1.87 KPa and 11.99 ± 2.01 KPa for the 6.0 mm screws. Thus, the 5.0 mm screw had lower pullout and higher shear stress, suggesting that this screw is more susceptible to loosening.